BANK CREDITS AND PERFORMANCE OF WOMEN ENTREPRENEURSHIP: EVIDENCE FROM BENUE STATE NIGERIA - Peter Ngbede, Ajam; Adah John, Emmanuel (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
This study examined the impact of bank loans on the entrepreneurial performance of women in the Otukpo Local Government Area of Benue State. The study analyzed the impact of collateral requirement, financial information required by banks, and interest rate levied by banks on the entrepreneurial performance of women in Otukpo Local Government Area, Benue State. The study employed a survey design, and a questionnaire was used to collect data. The population of Otukpo LGA consists of 109 female business proprietors. The research employed census sampling. For data presentation and analysis, simple percentages, the mean, and the standard deviation were utilized, while regression analysis was used to test hypotheses. The study found that collateral requirement, financial information required by banks, and interest rate levied by banks have a positive effect on the performance of women entrepreneurs in the Otukpo Local Government Area of Benue State. The study concludes that bank loans have a significant impact on the performance of Benue State women-owned enterprises. The study recommended that the Benue State government implement policies that facilitate SME credit.